(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article presents an in-depth analysis of common mental disorders, including depression, neuroses, and addictive conditions (alcoholism and drug addiction). Their epidemiological characteristics, biopsychosocial factors of development, and impact on public health and the economy are examined. Special attention is given to the problem of undiagnosed cases, the relationship between mental and somatic diseases, and the consequences of the COVID-19 pandemic. The results indicate a high prevalence of these disorders and the need to improve the system of psychiatric care.